SMALL EFFORT, BIG RESULTS: THROWING AND CATCHING ACTIVITIES USING PLASTIC BALL TO FOSTER CHILD'S KINESTHETIC ABILITY - Krobo, Andrianus (Journal of Early Childhood Education (JECE), 2021)
The purpose of this study was to improve the kinesthetic ability of group A, Ria Pembangunan Kindergarten, Sentani, Jayapura through a throwing-catching game using the small plastic ball. This research uses the action research method. Participants were collected using purposive sampling by involving 12 children in group A. Kinesthetic ability is one aspect that plays an essential role in child development. In the first cycle, the results showed that the child's kinesthetic ability reached 49.30%, including throwing with one hand over the shoulder, reaching 45.83%, throwing with one hand below 52.08%, and catching the ball 50%. As for the second cycle, it increased to 82.64%, including throwing with one hand over the shoulder, reaching 81.22%, throwing with one hand below, reaching 85.42%, and the aspect of catching the ball reaches 83.33%. Thus, the results showed that throwing-catching games using small plastic balls could improve the kinesthetic ability of group A at Ria Pembangunan Sentani Kindergarten, Jayapura Regency, Papua.